2016
DOI: 10.1371/journal.pone.0161407
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Predictions of Survival in Palliative Care: How Accurate Are Clinicians and Who Are the Experts?

Abstract: BackgroundPrognostic accuracy in palliative care is valued by patients, carers, and healthcare professionals. Previous reviews suggest clinicians are inaccurate at survival estimates, but have only reported the accuracy of estimates on patients with a cancer diagnosis.ObjectivesTo examine the accuracy of clinicians’ estimates of survival and to determine if any clinical profession is better at doing so than another.Data SourcesMEDLINE, Embase, CINAHL, and the Cochrane Database of Systematic Reviews and Trials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
182
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(209 citation statements)
references
References 65 publications
(192 reference statements)
7
182
3
4
Order By: Relevance
“…Several studies have shown that clinicians are generally over optimistic in their estimates of the prognoses of terminally ill patients [9] [5] [10] [11]. It has also been shown that no subset of clinicians are better at late stage prognostication than than others [12] [13] . However, clinician judgment remains the most common method of predicting survival in practice [12].…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have shown that clinicians are generally over optimistic in their estimates of the prognoses of terminally ill patients [9] [5] [10] [11]. It has also been shown that no subset of clinicians are better at late stage prognostication than than others [12] [13] . However, clinician judgment remains the most common method of predicting survival in practice [12].…”
Section: Related Workmentioning
confidence: 99%
“…Accurate prognosis is consistently shown to be important to patients, caretakers, and physicians from both a clinical decision standpoint but also an emotional standpoint (White et al, ). Cases like those described here are particularly concerning because physicians who overpredict early lethality have been shown to provide less resuscitation in the neonatal ICU potentially indicating that a poor prognosis can become a self‐fulfilling prophecy (Medlock et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] These wishes cannot be fulfilled if the clinical team are not able to recognise accurately that the person is dying. Although clinician predictions of survival are frequently inaccurate and overoptimistic, [7][8][9] they are still quite well correlated with actual survival and so are still recommended for use in routine clinical practice. 10 The 'More Care: Less Pathway' report into the limitations of the Liverpool Care Pathway (LCP) described, among other things, the dissatisfaction of relatives with the information they were given about how long their relative was expected to live.…”
Section: Introductionmentioning
confidence: 99%